A minute makes a difference: Apply countdown timers to cognitive well-being surveys - Zhou Fang; Yue-Mei-Tong Chen; Yong Bian (Acta Psychologica, 2023)
This paper implemented the use of countdown timers in online subjective well-being (SWB) surveys via an online experiment. The study involved 600 US residents who were equally divided into two groups: a control group and an experimental group. Both groups were posed with the same question, “All things considered; how do you rate your own life satisfaction?” However, the experimental group was subjected to a 1-minute countdown timer before submitting their responses, while the control group was not. Our findings indicate that incorporating timers into online surveys can effectively prevent participants from mis-responding by distinguishing between their affective and cognitive well-being. Furthermore, the use of timers resulted in more comprehensive responses, as participants were able to engage in deeper reflection on their life and consider a wider range of factors.